The Influence of Social Skills and Innovation Ability on Students' Entrepreneurial Attitudes in the Higher Grades of Public Elementary Schools - Khadijah Khadijah; Syarifuddin Syarifuddin; Saripuddin Saripuddin; Erni Rismawanty (EDUJAVARE: International Journal of Educational Research, 2026)
Social skills produce positive and beneficial interactions for each individual. This study aims to: determine and analyze the simultaneous influence of social skills and innovation abilities on the entrepreneurial attitudes of senior students at Lumu-Lumu Public Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City. This research approach uses quantitative research. This research was conducted at Lumu-Lumu Public Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City. The population of this study was 52 senior students (grades 4, 5, and 6) at Lumu-Lumu Public Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City. This study used saturated sampling, or population sampling, by taking the entire population as a sample, resulting in a sample of 52 students. The data collection technique used a questionnaire, and the data analysis technique used multiple regression techniques and t-test analysis. Testing was carried out using SPSS 26. The results of this study indicate that; 1). Social skills have a positive and significant influence on the entrepreneurial attitudes of senior students at Lumu-Lumu Public Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City. 2). Innovation ability (X2) has a positive and significant influence on the entrepreneurial attitudes of upper-grade students of Lumu-Lumu State Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City. 3). Social skills and innovation ability jointly influence the entrepreneurial attitudes of upper-grade students of Lumu-Lumu State Elementary School, Ujung Tanah District, Sangkarrang Islands, Makassar City.